Concentration, fluxes, risks, and sources of heavy metals in atmospheric deposition in the Lihe River watershed, Taihu region, eastern China. (December 2019) - Chen, Lian; Zhou, Shenglu; Wu, Shaohua; Wang, Chunhui; He, Di
Abstract: This study investigated ecological and human-health risks associated with heavy-metal pollution arising from deposition in the Lihe River region of eastern China. Ecological risk assessment was based on the geoaccumulation index and health risk using a US Environmental Protection Agency health risk assessment model. Pollution source contributions were assessed through enrichment factors, positive matrix factor analysis, and Pb isotopic analyses. Mean concentrations of Cd, Cr, Cu, Ni, Pb, and Zn measured in deposited particulates were 8.842, 79.92, 150.3, 46.86, 231.7 and 1920 mg kg −1, respectively. Deposition fluxes of these six heavy metals were 0.6, 6.0, 10.9, 3.3, 16.4, and 157 mg m −2 a −1, respectively. The order of ecological risk was Cd > Zn ≈ Pb > Cu > Ni > Cr. Ingestion is the main pathway of human exposure, however hazard quotient and hazard index values of the heavy metals studied were <1, indicating little or minimal risk to human health. The contributions to atmospheric deposition of coal-fired industries were Cd 82.4%, Cu 51.9%, Ni 51.2%, and Pb 68.3%. Zn was derived mainly from vehicular emissions (75.7%), and Cr concentrations (66.3%) were controlled mainly by natural sources. The qualitative and quantitative methods employed here resulted in improved accuracy of source apportionment. The results provide insights into the management of heavy-metal pollution in atmospheric deposition and serve as a reference for other regions of China. Graphical abstract: Image 1 Highlights: Cd, Cr, Cu, Ni, Pb, and Zn concentrations were 8.8, 80, 15, 47, 232 and 1920 mg kg −1 . Their fluxes were 0.6, 6.0, 10.9, 3.3, 16.4, and 157 mg m −2 a −1, respectively. The order of ecological risk was Cd > Zn ≈ Pb > Cu > Ni > Cr. HQ and HI were both <1 and ingestion is the main pathway of human exposure. Except for Cr, human activities were the largest dominator with contributions of >50%. Abstract : According to our findings, heavy metals in deposition posed little health risk; Except for Cr, human activities were the largest dominator, with contributions of >50%.